A methodology for evaluating the manganese tolerance of cowpea (Vigna unguiculata) and some preliminary results of field trials - Kang, B.T.; Fox, R.L. (1980)
Cowpeas (162 cultivars) were grown across soil pH gradient (4.8–7.1) which had been established by liming a manganiferous Oxisol of Hawaii. In the early stages of growth low soil pH was associated with chlorosis of the first trifoliate leaves of some cultivars. A more frequently observed symptom was a “freckling” on the unifoliate and first trifoliate leaves. Many varieties growing in acid soil developed multiple shoots in petiole axes after flowering. This symptom, when severe, was always associated with aborted flowers. The Mn contents of 35-day-old cowpea tops, grown at three pH levels, ranged from 600 to 2800 μg/g. As a group, cultivars which responded most to lime additions, if they were not limed, contained almost twice as much Mn as the nonresponsive group. The maximum Mn content of young cowpea at which growth was possible was in the range 2500–2800 μg/g. Cultivars which responded to lime fixed increasing amounts of N with increasing soil pH (decreasing plant Mn). The most vigorously growing young plants contained about 1000 μg Mn/g plant top. In nutrient solution culture this Mn content was associated with 1–2 μg Mn/ml of nutrient solution. Potential yield of the cultivars at pH 4.8 and at the most favorable pH was estimated from regression curves of yield vs. distance across the lime variable. Responsiveness to lime was evaluated by the slope of the regression line. A scheme which classified cowpea for tolerance to Mn was developed. The scheme had five main groups based on yield potential at the most favorable soil pH for each cultivar and three subgroups based on yield potential at pH 4.8. Responsiveness to lime was indicated by the order of listing within subgroups. Based on this scheme 10 cultivars qualified for subgroup A1 which required a yield potential > 1500 kg/ha at optimum pH and yield potential > 50% of maximum at pH 4.8.